Kontribusi Kegemukan dan Resistensi Insulin dalam Perkembangan Sindrom Ovarium Polikistik: Suatu Kajian Pustaka - Janu, Juwana; Dini Mardhiyani (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Polycystic Ovary Syndrome (PCOS) is a complex endocrine disorder affecting reproductive-age women and is closely associated with metabolic disturbances such as overweight and insulin resistance. More than 50% of women with PCOS are overweight, which exacerbates ovulatory dysfunction and increases androgen levels. Insulin resistance, found in approximately 50% of PCOS patients—even those with normal body weight—triggers hyperinsulinemia that stimulates androgen production and suppresses ovulation. This study aims to analyze the contribution of overweight and insulin resistance to the development of PCOS through a literature review approach. Scientific articles were retrieved from databases such as PubMed and Google Scholar, focusing on publications from the last five years. The findings indicate that overweight and insulin resistance mutually reinforce hormonal and ovulatory dysfunction typical in PCOS patients. Recent studies show that higher body mass index (BMI) and elevated HOMA-IR levels are strongly associated with menstrual irregularities, hyperandrogenism, and reduced quality of life. In conclusion, overweight and insulin resistance are two major contributing factors to PCOS pathogenesis and influence reproductive success. Clinical management should consider a comprehensive approach targeting both factors through lifestyle interventions and pharmacological therapy.